Vankila - Gorky, Maksim, 1868-1936; Lattu, Iisakki, 1857-1932 (Salt Lake City, UT : Project Gutenberg, 2016)
"Vankila" by Maksim Gorky is a novel written in the early 20th century. The story focuses on Mischa Malinin, a student who finds himself entangled in the oppressive and tumultuous environment of a prison amidst a politically charged atmosphere. It explores themes of social injustice, the human spirit, and the quest for dignity in the face of adversity. The opening of "Vankila" sets a grim and atmospheric scene as a crowd is being forcefully herded into a prison surrounded by a chilly, oppressive weather. Mischa, described as a compassionate and sensitive young man, is caught up in the chaotic turmoil of the people around him, some fearful, others defiant. He bravely confronts a police officer when he sees a young girl being pushed against her will, demonstrating his inner turmoil and overwhelming sense of empathy. The narrative introduces various characters and an eerie atmosphere of despair while hinting at the underlying social tensions and the personal struggle of Mischa, as he grapples with the harsh realities of life in captivity. (This is an automatically generated summary.)
Release date is 2016-11-23
E-text prepared by Tapio Riikonen
Keywords: Russian fiction -- Translations into Finnish